Algebra: A Combined Approach (4th Edition)

Published by Pearson
ISBN 10: 0321726391
ISBN 13: 978-0-32172-639-1

Chapter 5 - Review - Page 407: 136



Work Step by Step

$(7x-2)(4x-9)=$ $7x(4x-9)-2(4x-9)=$ $7x(4x) + (7x)(-9) -2(4x) -2(-9)=$ $28x^{2}-63x-8x+18=$ $28x^{2}-71x+18$
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.